Deterioration of Vestibular Cells in Labyrinthitis. (February 2017) - Kaya, Serdar; Schachern, Patricia A.; Tsuprun, Vladimir; Paparella, Michael M.; Cureoglu, Sebahattin
Objective: To quantitatively assess the effect of serous labyrinthitis, suppurative labyrinthitis, and labyrinthitis ossificans on vestibular hair cells, dark cells, and transitional cells. Methods: We examined human temporal bone specimens with serous labyrinthitis, suppurative labyrinthitis, and labyrinthitis ossificans, then compared them with age-matched control groups without labyrinthitis. We evaluated the density of type I and II vestibular hair cells, dark cells, and transitional cells in the peripheral sensorial organs. Results: The mean density of type I vestibular hair cells in the maculae of the saccule significantly differed between the serous labyrinthitis group and its control group. The loss of type I and II vestibular hair cells in all of the peripheral sensorial organs was significantly higher in the suppurative labyrinthitis group than in its control group. The mean density of dark cells in the lateral and posterior semicircular canals was significantly lower in the suppurative labyrinthitis group than in its control group. The mean density of type I and II vestibular hair cells, dark cells, and transitional cells was significantly lower in the labyrinthitis ossificans group than in its control group. Conclusion: The loss of vestibular hair cells and degenerative changes in dark cells and transitional cells could affect vestibular function in patients with labyrinthitis.